The Role of Mineral and Synbiotic to Enhance Immunity During Covid-19 Pandemic : A Literature Review - Setyaningtyas, Stefania Widya; Atmaka, Dominikus Raditya; Rachmah, Qonita; Haryana, Nila Reswari; Rifqi, Mahmud Aditya; Diana, Rian; Nastiti, Aliffah Nurria; Agustin, Asri Meidyah (Universitas Airlangga, 2023)
COVID-19 has become a pandemic in the last 3 years worldwide and cases cause high mortality and morbidity. To reduce COVID-19 infection, we need to keep our immune system healthy. Several nutrients have been shown to have specific abilities to increase the power of the immune system, but their use in the treatment of COVID-19 is still being debated. This review aims to determine the role of minerals and synbiotics in increasing immunity during the COVID-19 pandemic. Specific minerals such as zinc, selenium, iron and copper have promising potential to treat COVID-19 by reducing clinical impact, markers of inflammation, and improving immunological biomarkers. In addition to increasing mineral intake, maintaining a healthy immune system can also be done by improving the health of the gut microbiota. One of the therapies that is considered to have a positive impact on handling COVID-19 is using synbiotics (a combination of prebiotics and probiotics). However, the safety and efficacy of mineral and synbiotic supplementation in COVID-19 patients as adjunctive therapy still requires further research. Minerals and synbiotics can help boost the immune system and reduce symptoms during a COVID-19 infection.